Distribution patterns of N6-methyladenine in the rye genome - Anna Kalinka; Danuta Cembrowska-Lech; Marta Starczak; Daniel Gackowski (Scientific Reports)
Abstract N6-methyladenine (6 mA) has emerged as a potential epigenetic marker in eukaryotic genomes, yet its precise distribution patterns and biological functions in plant genomes are still not fully understood. In this study, we investigated the occurrence, global levels, and distribution patterns of 6 mA in four rye species: Secale cereale, S. strictum, S. sylvestre, and S. vavilovii. Using multiple complementary approaches, i.e., ELISA, ultra-performance liquid chromatography tandem mass-spectrometry (UPLC-MS/MS), immunofluorescence, and high-throughput sequencing (PacBio and MeDIP-seq), 6 mA was detected in all the examined species. The level of 6 mA in the genomic DNA of the rye species, depending on the species and organ, ranged from approximately 1 to 10 per million nucleotides. Immunofluorescence revealed specific chromosomal distribution patterns of 6 mA. The 6 mA signal in the rye chromosomes was dispersed along all chromosome arms, while no 6 mA signals were detected in the centromeric and telomeric regions, indicating that large blocks of constitutive subtelomeric and pericentromeric heterochromatin along with functional telomeric and centromeric regions do not contain 6 mA residues. To precisely map the genomic distribution of 6 mA, a machine learning approach combining PacBio methylation calls with MeDIP-seq data was developed, which enabled the identification of 6 mA-enriched regions across the genomes of all the four rye species. The findings provide comprehensive insights into the presence and distribution of 6 mA in the rye genomes, contributing to the growing understanding of this modification’s potential role in the plant epigenetic regulation.